2016
DOI: 10.1177/1091581816648906
|View full text |Cite
|
Sign up to set email alerts
|

The MTT and Crystal Violet Assays

Abstract: The toxicological effects of nanoparticles (NPs) on humans, animals, and environment are largely unknown. Assessment of NPs cytotoxicity depends on the choice of the test system. Due to NPs optical activity and absorption values, they can influence the classical cytotoxicity assay. Eight NPs were spiked in the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and crystal violet assays and tested with HaCaT human skin cells. The MTT assay standard curve optical density (OD) measurements were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 58 publications
0
30
0
1
Order By: Relevance
“…αCD was chosen for the possibility to easily design a fucoside that matches FleA valency with all six sugars presented on the primary face. Polyhedral silsesquioxanes are emerging as versatile platforms for the design of multivalent compounds; furthermore, pharmaceutical studies suggest that the organosilica core has low intrinsic toxicity . Here, COSS functionalization should allow for a homogeneous distribution of the grafted sugars.…”
Section: Resultsmentioning
confidence: 99%
“…αCD was chosen for the possibility to easily design a fucoside that matches FleA valency with all six sugars presented on the primary face. Polyhedral silsesquioxanes are emerging as versatile platforms for the design of multivalent compounds; furthermore, pharmaceutical studies suggest that the organosilica core has low intrinsic toxicity . Here, COSS functionalization should allow for a homogeneous distribution of the grafted sugars.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of S-FLG or L-FLG on cell viability was measured by MTT assay. 62 A detailed experimental description is provided in the SI. S-FLG or L-FLG was added to the bacterial culture yielding a final nominal graphene concentration of 250 μg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, characterization regarding interference of NMs with the applied assay system is highly recommended. It has been shown that some NMs interfere with fluorescence/absorption in widely used assays such as alamarBlue™, Neutral Red or WST-1, which can lead to false positive cytotoxicity results unless interference test is included in the test [ 107 , 108 ].…”
Section: Nanomaterials–characteristics In Cell Culture Media and Amentioning
confidence: 99%